South America's tropopause variability in relation to global teleconnection (2001–2017): A GNSS-radio occultation assessment. (1st November 2020) - Nascimento, A.A.; Awange, J.L.; Gonçalves, R.M.; Khandu,
Abstract: Analysing tropopause variability is widely acknowledged to inform the understanding of global/regional warming. Tropopause variability studies are generally undertaken where radiosonde data abound. For the radiosonde data deficient South American continent, taking advantage of atmospheric remote sensing using Global Navigation Satellite Systems - Radio Occultation (GNSS-RO) could offer the means to understand its tropopause variability. In this study, 622, 914 GNSS-RO measurements of Challenging Minisatellite Payload (CHAMP), Gravity Recovery and Climate Experiment (GRACE) and Constellation Observing System for Meteorology Ionosphere & Climate (FORMOSAT-3/COSMIC), from 2001 to 2017 are used to analyze the annual variability patterns of tropopause heights and temperatures over South America and its relation to global teleconnections. Firstly, the RO measurements are validated using atmospheric profiles for 54 radiosonde stations across the continent. The results show increased trend of 13.450  ±  39.577 m/dec for the tropopause height and a corresponding slow decrease in temperature of −0.021  ±  0.115 K/dec, both statistically insignificant (i.e., p-value test) at 95% of confidence level (two-tailed student's t-test). The first mode of PCA (Principal Component Analysis) of the tropopause anomalies (of temperatures and heights) present significant temporal correlation (at 95% confidence level) with the ENSO 1 + 2 (El Niño–Southern Oscillation) index (i.e., a correlation coefficient of 0.6). The South America tropopause, therefore, varies over time albeit with slow changes and trends. This contribution highlights the importance of its monitoring. Graphical abstract: Image 1 Highlights: Insignificant tropopause height increase (13.450 ± 39.577 m/dec) obtained for the 2001–2017 period. Tropopause temperature slowly decreased by 0.021 ± 0.115 K/dec over the same period. Significant temperature correlation (0.60) obtained from EOF1 with the ENSO 1 + 2.